O ouro atua como hedge ou valor refúgio diante de variações cambiais negativas extremas? Evidências empíricas no mercado brasileiro - BRITO, Ademir Luis Teles (2016)
This dissertation investigates the gold protective properties in extreme situations depreciation of the Brazilian currency against the dollar. It analyzed empirically gold capacity mitigate the risk of exchange extreme volatility. For this purpose, maximum likelihood function is used on the conditional dependence structure of joint distributions of gold and foreign exchange in the period from 04 January 2000 to 20 February 2015. It concluded It was found that gold acts as a hedge against the depreciation of the Brazilian currency, as it is poor value refuge from extreme negative movements of the forex market. Evidence of the research indicated that add gold to the portfolio would provide diversification benefits, hedge and haven value because the gold showed a strong tendency to remain in a non-extreme state, or, acting as a hedge while the real depreciated against the dollar.